Blood cultures contaminated: “Bundle to achieve acceptable proportions” (Actualizaciones en Sida e Infectología, 2024)
Introduction. The problem of blood cultures contamination is very frequent in hospital care, it leads to the administration of unnecessary antibiotics and prolongs hospitalization. Main goal. To apply a bundle to reduce the proportion of blood culture contamination. Secondary objectives. Carry out an anonymous survey to detect improvement opportunities in the blood culture extraction technique. Methodology. Study design: Quasi-experimental study that evaluated the proportion of blood culture contamination before and after implementing an own Bundle. The baseline proportion of blood culture contamination was determined (Jan-July 2022), the intervention was performed (August 2022) and the post-intervention contamination proportion was established (Sep-April 2023). Intervention: The structure, procedure, and staff knowledge were analyzed through an own survey to detect improvement areas. Laboratory technicians were trained on the sampling procedure through a simulation using an artificial arm. A six measurements bundle´s was designed, the blood culture taking procedure was adapted, and the staff was trained. Statistical analysis. The proportion of contaminated blood cultures between the pre and post periods was analyzed using Chi2 and the relationship between the proportion of the pre and post period vs the literature (3.00% acceptable contamination) using the Z test for a proportion. A p
Keywords: Blood culture contamination Blood specimen collection Extraction of blood cultures